PENGARUH TRANSFER PRICING TERHADAP AGRESIVITAS PAJAK DI PERUSAHAAN MULTINASIONAL - Siahaya, Princessa; Lingga, Ita Salsalina (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2024)
Transfer pricing is a pricing method used in transactions between companies within the same group with the aim of optimizing global profits through favorable pricing agreements. This strategy is commonly used by multinational companies to reduce tax liabilities by transferring income to jurisdictions with lower tax rates, thereby potentially increasing tax aggressiveness. The investigation conducted in this study examines the correlation between transfer pricing and tax aggressiveness, focusing on PT Adaro Energy Tbk as a case study, which is a multinational energy company based in Indonesia. The main objective of this investigation is to assess transfer pricing in relation to the tax behavior of multinational companies. Using the Systematic Literature Review (SLR) methodology, this research involves compiling various journals accredited by SINTA. The findings lead to the conclusion that transfer pricing does not have a significant impact on the tax behavior of multinational companies. Consequently, the authors propose the introduction of additional variables to evaluate tax behavior in multinational companies. This discovery emphasizes the need for enhanced regulation and oversight of transfer pricing practices by tax authorities to ensure compliance and equity in the tax system.